Electronic Collaboration of Strategic Performance Management System (SPMS), Normative Funding (NF), and Organizational Performance Indicator Framework (OPIF) for Technological University of the Philippines - Mangaba, Joel B. (International Journal of Computing Sciences Research, 2017)
Purpose – The study of developing an integrated performance management aims to link planning, budgeting, and accountability elements of the performance management cycles in the university and to attain the effort of the GoP to develop a unique model of performance-based budgeting known as the Organizational Performance Indicator Framework (OPIF) in collaboration with other models of performance management Strategic Performance Management System (SPMS) and Normative Funding (NF) used by the university. To support the requirements for different agencies, this study aimed  to develop and implement an Electronic Collaborative System that would contain the graphical user interface (GUI) and database definition and manipulation for the computerization on the implementation of SPMS, NF, and OPIF as one. Method – To meet the efficiency and effectiveness of the system, System Development Life Cycle was used as the method of developing the system because of the practicality of its stages to follow from an initial data gathering through maintenance of the completed project. Series of performance tests under different conditions were conducted to measure the functionality, reliability, usability, and efficiency of the software project. Results – The overall mean 4.16 gives the general interpretation that the study is accepted. This is the result of the mean scores per respondents from different criteria such as functionality, reliability, usability, and efficiency. The average mean ratings of possible users, IT experts, and personnel of the Planning Office are 4.50, 3.97, and 4.00, respectively. Conclusions – The findings of the study proved that the developed software is acceptable based on the indicators. Recommendations – The recommendations of the evaluators given based on the analysis of the study are: to conduct more tests in order to improve the efficiency of the system and in order to identify the possible enhancement of the functionality; to conduct an in-depth study to test whether the system project developed for TUP can be integrated to the existing system like ERS and Portal; maintain the system and monitor possible errors that were not anticipated in the previous study; and to conduct other researches with other SUCs for the possible implementation of the system in a national level with consideration on the availability of IT infrastructure. Practical Implications – This study can be used by different SUCs sectors in decision making on how to better improve the performance of the institution aligned with the Success Indicators assigned to academic and can be easily validated and verified with the requirements of CHED and DBM. The collaboration of the requirements allows greater coordination between and among the management and the academic personnel.